Carbon-free cathode for lithium-sulfur battery

By using carbon-free sulfur cathode material and non-carbon metal chalcogenide in lithium sulfur batteries, combining core-shell structure and intercalation materials, the problem of insufficient energy density and mechanical stability in lithium sulfur batteries is solved, and high energy density is achieved and low-cost lithium-sulfur battery design.

CN119301787APending Publication Date: 2025-01-10CONAMIX INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380043833.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2023-04-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The energy density of the sulfur cathode in existing lithium-sulfur batteries is low and the mechanical stability is insufficient, mainly due to the problems of inhibiting lithium ion transmission and reducing energy density due to carbon additives, and the use of cobalt and nickel has supply and environmental problems.

Method used

Carbon-free sulfur cathode materials, including electroactive sulfur materials and non-sulfur, non-carbon materials, such as metal chalcogenides, are used to improve lithium ion transportability and mechanical stability, and are used to provide specific voltages through core-shell structures and intercalation materials. Lithium ions are reversiblely embedded within range.

Benefits of technology

It improves the energy density and mechanical stability of lithium-sulfur batteries, reduces dependence on cobalt and nickel, reduces costs, and avoids the negative impact of carbon additives on electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301787A_ABST
    Figure CN119301787A_ABST
Patent Text Reader

Abstract

Presented herein is a cathode material for a carbon-free (including relatively carbon-free) cathode comprising (i) sulfur and / or lithium sulfide and (ii) a different non-carbon electroactive material, such as a metal chalcogenide. In certain embodiments, it was found that the carbon-free cathode material facilitates improved ion transport while maintaining satisfactory mechanical stability and electrical connectivity of the cathode without the use of conductive carbon additives.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 331,245, filed on April 14, 2022, the contents of which are hereby incorporated by reference in their entirety. Background Art

[0003] There is a lot of work going on to develop lithium-ion batteries with high energy density, long cycle life, and low cost, especially for use in electric vehicles and consumer electronics.

[0004] Sulfur is a low-cost, high-specific-energy material that is a byproduct of the oil and gas industry. Research into sulfur-based battery cathodes has been ongoing for some time. As a high-energy-density cathode material, sulfur has the potential to eliminate the need for cobalt and nickel in lithium batteries. Cobalt is expensive, toxic, and cobalt mining in some regions can be subject to loose regulation and unethical practices. Nickel has a high energy density, but there are concerns about its supply in the long term, such as the recent move by Tesla to move away from nickel-containing batteries.

[0005] Producing sulfur cathodes that can achieve commercial performance levels has been a challenge, for example, because sulfur byproducts can degrade performance and limit cycle life, and low-density single-functional materials such as conductive carbon additives can negatively impact the energy density of formulated sulfur cathodes.

[0006] The cathode of a lithium battery, including a lithium-sulfur battery cathode, almost always contains conductive carbon. For example, conductive graphite additives are often introduced to enhance the mechanical stability and electronic conductivity of the cathode. However, carbon has poor lithium ion transport properties (e.g., the transport of lithium ions through the cathode pore network may be hindered by this carbonaceous mixed phase) and does not contribute to the electrochemical capacity of the battery. In addition, due to the low weight density of carbon, its presence significantly reduces the volumetric energy density of the sulfur cathode composite. Attempts have been made to improve low ionic conductivity. For example, the use of conductive carbon-sulfur films with interconnected mesopores has been studied as advanced cathodes for lithium-sulfur batteries.

[0007] However, this does not solve the problem of reduced energy density, and there is still a need for cathode compositions with satisfactory mechanical stability and electrical properties in lithium-sulfur batteries to overcome the problems of lithium ion transport inhibition and reduced energy density caused by the carbon-containing phase in the cathode. Summary of the invention

[0008] The present disclosure provides, inter alia, cathode materials and batteries comprising the cathode materials.The cathode material can include at least one electroactive sulfur material and one non-sulfur, non-carbon material (eg, wherein the cathode material is substantially free of carbon).

[0009] In some aspects, the present disclosure relates to cathode materials for a carbon-free sulfur cathode, the cathode material comprising: at least one electroactive sulfur-conversion cathode material; and a non-sulfur, non-carbon electroactive material, wherein the cathode material (e.g., and wherein the carbon-free cathode) contains no more than 5 wt % (e.g., no more than 2 wt %, no more than 1 wt %, no more than 0.5 wt %, or no more than 0.1 wt %) carbon.

[0010] In some embodiments, the non-sulfur, non-carbon electroactive material is an intercalation material that has the ability to convert sulfur to an electrochemical state over a voltage range that overlaps the voltage range of sulfur conversion (e.g., about 1.8 V to about 2.6 V vs. Li / Li). + , for example, about 2.0 V to about 2.4 V, relative to Li / Li + ) structure that can reversibly embed lithium ions.

[0011] In some embodiments, the non-sulfur, non-carbon electroactive material is a conversion material (e.g., in a voltage range that overlaps with the voltage range for sulfur conversion (e.g., about 1.8 V to about 2.6 V vs. Li / Li + , for example, about 2.0 V to about 2.4 V, relative to Li / Li + )Sulfur compounds that undergo electrochemical conversion reactions).

[0012] In some embodiments, the non-sulfur, non-carbon electroactive material is a chalcogenide (eg, a metal chalcogenide, eg, a metal sulfide).

[0013] In some embodiments, the non-sulfur, non-carbon electroactive material is also an electron conductor.

[0014] In some embodiments, the non-sulfur, non-carbon electroactive material has a discharge capacity.

[0015] In some embodiments, the cathode material comprises a core-shell structure. In some embodiments, the cathode material comprises a core each having a surrounding shell, the core comprising an electroactive sulfur conversion material (e.g., Li2S2 and / or Li2S), and the shell comprising a non-sulfur, non-carbon electroactive material (e.g., one or more metal chalcogenides).

[0016] In some embodiments, the core-shell structure has an average core diameter in the range of 50 to 300 nm and an average shell thickness in the range of 1 to 20 nm thick (eg, no greater than 10 nm thick).

[0017] In some embodiments, the core-shell structure has at least 10 mass % of non-sulfur, non-carbon electroactive material (e.g., metal chalcogenide) relative to sulfur (e.g., 10 to 90 mass % of non-sulfur, non-carbon electroactive material, e.g., 30 to 70 mass % of non-sulfur, non-carbon electroactive material).

[0018] In some embodiments, the electroactive sulfur-conversion cathode material comprises one or more members selected from the group consisting of sulfur in the form of an S8 cyclic octaatomic molecule, lithium sulfide (e.g., Li2S2 and / or Li2S), an electroactive organosulfur compound, and an electroactive sulfur-containing polymer.

[0019] In some aspects, the present invention is directed to a cathode comprising any cathode material described herein, wherein the fraction of carbon in the cathode does not exceed 5 wt % (e.g., does not exceed 2 wt %, does not exceed 1 wt %, does not exceed 0.5 wt %, or does not exceed 0.1 wt %).

[0020] In some embodiments, the cathode material is disposed in a thin film (eg, including a binder).

[0021] In another aspect, the invention relates to a battery (eg, a rechargeable battery) comprising (i) a cathode as described herein and (ii) an electrolyte in contact with the cathode.

[0022] In some embodiments, the battery further comprises an anode. In some embodiments, the anode is a protected lithium metal anode.

[0023] In some embodiments, the battery further includes a protected current collector.

[0024] Any two or more of the features described in this specification (including in this summary) may be combined to form an embodiment of the present disclosure, regardless of whether or not specifically and explicitly described as a separate combination in this specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] When with Figure 1 The teachings of the present invention described herein will be more fully understood from the following description of various exemplary embodiments when read together. It should be understood that the figures described below are for illustrative purposes only and are not intended to limit the scope of the teachings of the present invention in any way. The foregoing and other objects, aspects, features and advantages of the present disclosure will become more apparent and can be better understood by reference to the following description taken in conjunction with the accompanying drawings, in which:

[0026] Figure 1 illustrates a cross-section of an electrochemical cell 800 according to an exemplary embodiment of the present disclosure; and

[0027] Figure 2 Examples of batteries according to various embodiments described herein are illustrated.

[0028] definition

[0029] About / approximately: When used herein to refer to a certain value, the term "about" or "approximately" refers to a value similar to the value referred to in the context. Generally speaking, those skilled in the art who are familiar with the context will understand the relevant degree of difference covered by "about" or "approximately" in the context. For example, in some embodiments, for example, as described herein, the term "about" can be included in a series of values ​​within a portion of 25%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or one percent of the value referred to.

[0030] Carbon: As used herein, in relation to cathode materials, refers to elemental carbon or materials consisting essentially of elemental carbon, examples of which include graphite, carbon black, graphene, carbon nanotubes, and derivatives of such materials (e.g., oxidized, nitrogen-doped, or carboxylated graphene derivatives). Unless otherwise indicated, this term does not encompass carbon-containing organic molecules such as hydrocarbons, polymers, solvents, etc. Similarly, in the context of terms such as "carbon-free" and "non-carbon materials", these elemental forms of carbon should be understood to be excluded.

[0031] Intercalation Material: As used herein, the term "intercalation material" refers to a substance in which another substance or species (e.g., ions, metal ions) is reversibly inserted or contained in vacancies, interstitial sites, voids, between layers of the intercalation material, or some combination thereof.

[0032] Electroactive Material: As used herein, the term "electroactive material" refers to a composition of matter having one or more components that are capable of changing their oxidation state during the charge transfer step of an electrochemical reaction.

[0033] Lithium alloy: As used herein, the term lithium alloy refers to substances formed by the combination of lithium with other metallic or semi-metallic elements: non-limiting examples include lithium silicon compounds and alloys of lithium with metals such as sodium, cesium, indium, aluminum, zinc and silver.

[0034] Nanoparticles, nanostructures, nanomaterials: As used herein, these terms can be used interchangeably to refer to particles of nanoscale size or materials with nanoscale structures. Nanoparticles can have essentially any shape or configuration, such as tubes, wires, laminates, sheets, grids, boxes, cores and shells, or combinations thereof.

[0035] Substantially: As used herein, the term "substantially" refers to the qualitative condition of exhibiting the full or nearly full extent or degree of a characteristic or property of interest. DETAILED DESCRIPTION

[0036] The elements of the different implementations described herein can be combined to form other implementations not specifically described above. Elements can be deleted from the devices described herein without adversely affecting their operation. Various separate elements can be combined into one or more separate elements to perform the functions described herein.

[0037] It is contemplated that the claimed inventions, articles, devices, compositions, systems, methods, and processes encompass variations and adaptations developed using information from the embodiments described herein. Adaptations and / or modifications of the articles, articles, devices, compositions, systems, methods, and processes described herein may be performed as contemplated by this specification.

[0038] Throughout this specification, where articles, devices, compositions, and systems are described as having, comprising, or comprising particular components, or where processes and methods are described as having, comprising, or comprising particular steps, it is contemplated that there are additional articles, devices, compositions, and systems of the invention that consist essentially of, or consist of, the recited components, and that there are processes and methods of the invention that consist essentially of, or consist of, the recited steps.

[0039] It should be understood that the order of steps or the order in which certain actions are performed is not important, as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0040] The mention of any publication herein is not an admission that the publication serves as prior art to any claim presented herein.The Background section is presented for purposes of clarity and is not meant as a description of prior art with respect to any claim.

[0041] Headings are provided for the convenience of the reader—the presence and / or placement of headings is not intended to limit the scope of the subject matter described herein.

[0042] A cathode material for producing a carbon-free (including relatively carbon-free) cathode is presented herein, the cathode material comprising (i) a sulfur-based active material and (ii) a different non-carbon electroactive material, such as a metal chalcogenide. In certain embodiments, it is found that the carbon-free cathode material is advantageous for improving ion transport while maintaining satisfactory mechanical stability and electrical conductivity of the cathode without the use of graphite additives or other carbon additives.

[0043] In certain embodiments, the non-carbon electroactive material is an intercalation material that is capable of operating in a voltage range that roughly corresponds to the sulfur to lithium sulfide conversion voltage (e.g., about 1.8 V to about 2.6 V, relative to Li / Li + , for example, about 2.0 V to about 2.4 V, relative to Li / Li +) reversibly intercalates lithium ions. Intercalation is the process of reversibly incorporating mobile ions or molecules into vacancies in the host network lattice. The general characteristics of the intercalation process are minimal volume changes and mechanical strains during repeated insertion and extraction of ions during charge and discharge. Intercalation cathode materials contain a solid host network that can reversibly store guest ions that are inserted into and removed from the host network.

[0044] In addition, in certain embodiments, cathode material has core-shell structure (for example, nanostructure), wherein core contains sulfur active material and the shell around it contains non-carbon electroactive material.In certain embodiments, the structure is nanoporous.In certain embodiments, the average diameter of core is, for example, less than about 1000nm, less than about 500nm, less than about 250nm, less than about 100nm, less than about 80nm, less than about 70nm, less than about 60nm, less than about 50nm, less than about 40nm, less than about 30nm, less than about 25nm, less than about 20nm, less than about 10nm or less than about 5nm, and / or the average diameter of core can be between any two of the above listed values ​​in any range.In certain embodiments, the shape of core is spherical, coarse spherical or amorphous.In certain embodiments, the average diameter of core is between about 50 to about 500nm, between about 50 to about 200nm, between about 20 to about 100nm, between about 100 to about 300nm or between about 200 to about 400nm.

[0045] In certain embodiments, the average thickness of the shell around the core is, for example, less than about 1000nm, less than about 500nm, less than about 250nm, less than about 100nm, less than about 80nm, less than about 70nm, less than about 60nm, less than about 50nm, less than about 40nm, less than about 30nm, less than about 25nm, less than about 20nm, less than about 15nm, less than about 10nm, less than about 5nm, less than about 3nm, less than about 2nm or less than about 1nm, and / or the average thickness of the shell can be in any range between any two of the above listed values. In certain embodiments, the average thickness of the shell around the core is between about 1 to about 50nm, between about 2 to about 20nm, between about 1 to about 10nm, between about 10 to about 20nm, between about 5 to about 15nm or between about 1 to about 5nm.

[0046] In certain embodiments, the core of the provided core-shell particles consists of a substantially pure electroactive sulfur material. In certain embodiments, the core comprises a composite material of an electroactive sulfur material and an additional material (such as an inorganic solid, metal, polymer or other non-sulfur electroactive material). Such composite materials may comprise a simple physical mixture of materials or a more complex structural composite material, such as a porous scaffold infused with a sulfur electroactive material.

[0047] In certain embodiments, the non-carbon electroactive shell of the provided core-shell particles is non-porous and / or substantially impermeable to liquids (e.g., electrolytes) and / or impermeable to sulfur or polysulfides (or mixtures of electrolytes and polysulfides). This arrangement may be advantageous because it allows electrons and lithium ions to enter the electroactive sulfur core while preventing the electroactive sulfur material from being redistributed in the cathode or battery.

[0048] In other embodiments, the non-carbon electroactive shell of the core-shell particles provided is porous and / or permeable (e.g., permeable liquid electrolyte or its components). In certain embodiments, such permeable shells may be beneficial to ensure that the electrolyte is in contact with the electroactive sulfur and / or prevent the physical strain caused by the volume change in the core from rupturing or otherwise damaging the shell. In certain embodiments, such shells are nanoporous; for example, having a hole with a diameter less than 1nm; for example, less than 0.5nm, less than 0.4nm, or less than 0.3nm, or less than 0.2nm, and / or the average pore size is in any range between any two of the above listed values. In certain embodiments, the average pore size of the core and / or shell is less than 1nm; for example, less than 0.9nm, less than 0.8nm, less than 0.7nm or less than 0.6nm, and / or the average pore size is in any range between any two of the above listed values. In certain embodiments, the pore size is measured by a microscope (e.g., TEM, SEM, or AFM).

[0049] In certain embodiments, the non-carbon electroactive material comprises one or more chalcogenides. In certain embodiments, the chalcogenide has at least one chalcogen anion (oxygen, sulfur, selenium, tellurium or polonium anion) and at least one electropositive element. In certain embodiments, the chalcogenide can be based on sulfide, selenide or telluride. In certain embodiments, the chalcogenide comprises a metal sulfide (e.g., a sulfide of a metal other than lithium or sodium). In certain embodiments, one or more chalcogenides comprise a transition metal sulfide. In certain embodiments, one or more chalcogenides comprise one or more of the following: TiS2, LiTiS2 (LTS), VS2, MoS2, Mo6S8 and NbSe3. In certain embodiments, one or more chalcogenides comprise transition metal oxides and / or polyanionic compounds. In certain embodiments, one or more chalcogenides comprise a metal monochalcogenide having the formula MX, wherein M is a transition metal and X is S, Se or Te. In certain embodiments, the one or more chalcogenides include at least one transition metal dichalcogenide (TMD) of formula MX2, wherein M is a transition metal (e.g., Ti, V, Co, Ni, Zr, Nb, Mo, Tc, Rh, Pd, Hf, Ta, W, Re, Ir, or Pt), and wherein X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include a material having a layered crystal structure (e.g., LiTiS2, LiCoO2, LiNiO2, LiMnO2, LiNi 0.33 Mn 0.33 Co 0.33 O2、LiNi 0.8 Co 0.15 Al 0.05 O2 or Li2MnO3) and / or a material having a spinel crystal structure (e.g., LiMn2O4 or LiCo2O4).

[0050] In certain embodiments, the non-carbon electroactive material comprises an intercalation material and / or a non-sulfur, non-carbon electroactive material. For example, in certain embodiments, the non-carbon electroactive material comprises LiFePO4, LiMnPO4, or LiCoPO4 (e.g., having an olivine crystal structure), and / or LiFeSO4F or LiVPO4F (e.g., having a ferroxene crystal structure).

[0051] In some embodiments, the lithium-sulfur battery of the present disclosure includes a lithium anode, a sulfur-based cathode, and an electrolyte that allows ions to be transported between the anode and the cathode. In certain embodiments described herein, the anode portion of the battery comprises an anode and a portion of the electrolyte in contact with it. Similarly, in certain embodiments described herein, the cathode portion of the battery comprises a cathode and a portion of the electrolyte in contact with it. In certain embodiments, the battery includes a lithium ion permeable separator that defines a boundary between the anode portion and the cathode portion. In certain embodiments, the battery includes a housing that surrounds the anode portion and the cathode portion. In certain embodiments, the battery housing includes a conductive anode end cap electrically connected to the anode and a conductive cathode end cap electrically connected to the cathode to facilitate charging and discharging via an external circuit.

[0052] cathode

[0053] The compositions disclosed herein can be used to manufacture electrochemical devices. The disclosed compositions can be porous or non-porous. Certain compositions disclosed herein will adhere to a current collector to form a cathode of a secondary sulfur battery. Although the cathode described herein is intended to be carbon-free (including relatively carbon-free, for example, not more than 5% by weight of carbon, not more than 4% by weight of carbon, not more than 3% by weight of carbon, not more than 2% by weight of carbon, not more than 1% by weight of carbon, or not more than 0.5% by weight of carbon), some embodiments do contain some carbon. The cathode composition provided may include one or more additives, such as conductive particles, adhesives, and other functional additives commonly found in battery cathode mixtures. For example, in certain embodiments, the cathode composition provided may include 3D structured graphene (for example, as described in U.S. Patent No. 11,299,397 (LytEn, Inc.), the text of which is incorporated herein by reference in its entirety). In certain embodiments, the composition provided has satisfactory conductivity, thereby providing a low resistance path for the cathode, allowing electrons to enter the cathode manufactured in this way. In various embodiments, other additives are included in the composition to modify or otherwise enhance the cathode produced according to the principles described herein.Other cathode components include, for example, current collectors, tabs, and the like.

[0054] As discussed above, in certain embodiments, the cathode composition comprises a non-carbon electroactive material (e.g., an intercalation material) and a sulfur electroactive material, e.g., S8 Sulfur in the form of a cyclic octaatomic molecule, sulfur in the form of a lithium sulfide (e.g., Li2S2 and / or Li2S), and / or sulfur in the form of an electroactive organic sulfur compound or an electroactive sulfur-containing polymer. In certain embodiments, the electroactive material is an intercalation material configured to intercalate lithium ions. In certain embodiments, the electroactive material is in a voltage range that overlaps with the discharge voltage range of S8→Li2S (conversion of sulfur to lithium sulfide) (e.g., about 1.8 V to about 2.6 V, relative to Li / Li+ , for example, about 2.0 V to about 2.4 V, relative to Li / Li + )Work.

[0055] In certain embodiments, the electroactive material comprises one or more chalcogenides. In certain embodiments, the chalcogenide has at least one chalcogen anion (oxygen, sulfur, selenium, tellurium or polonium anion) and at least one electropositive element. In certain embodiments, one or more chalcogenides may be based on sulfide, selenide or telluride. In certain embodiments, one or more chalcogenides include metal sulfides. In certain embodiments, one or more chalcogenides include one or more of the following: TiS3, LiTiS2 (LTS), MoS2, Mo6S8, VS2, TaS2 and NbSe3. In certain embodiments, one or more chalcogenides include transition metal oxides and / or polyanionic compounds. In certain embodiments, one or more chalcogenides include metal monochalcogenides having the formula MX, wherein M is a transition metal and X is S, Se or Te. In certain embodiments, the one or more chalcogenides include at least one transition metal dichalcogenide (TMD) of the formula MX2, wherein M is a transition metal (e.g., Ti, V, Co, Ni, Zr, Nb, Mo, V, Tc, Rh, Pd, Hf, Ta, W, Re, Ir, or Pt), and wherein X is S, Se, or Te. In certain embodiments, the one or more chalcogenides include a material having a layered crystal structure (e.g., TiS2, CoO2, NiO2, MnO2, Ni 0.33 Mn 0.33 Co 0.33 O2, Ni 0.8 Co 0.15 Al 0.05 O2 or MnO3), materials having a spinel crystal structure (e.g., Mn2O4 or Co2O4), materials having an olivine crystal structure (e.g., FePO4, MnPO4 or CoPO4), and / or materials having a ferroxite crystal structure (e.g., FeSO4F or VPO4F). In certain embodiments, one or more chalcogenides include lithiated derivatives of materials having a layered crystal structure (e.g., LiTiS2, LiCoO2, LiNiO2, LiMnO2, LiNi 0.33 Mn 0.33 Co 0.33 O2、LiNi 0.8 Co 0.15 Al 0.05O2 or Li2MnO3), lithiated derivatives of materials having a spinel crystal structure (e.g., LiMn2O4 or LiCo2O4), lithiated derivatives of materials having an olivine crystal structure (e.g., LiFePO4, LiMnPO4 or LiCoPO4) and / or lithiated derivatives of materials having a hydroxyphospholipidite crystal structure (e.g., LiFeSO4F or LiVPO4F).

[0056] In certain embodiments, one or more non-carbon, non-sulfur electroactive materials are characterized in that they have high electronic conductivity. For example, the non-carbon, non-sulfur electroactive material has an electrical conductivity greater than about 10 -3 mS / cm 2 ; greater than about 0.01mS / cm 2 , greater than about 0.05mS / cm 2 , greater than 0.1mS / cm 2 , greater than 0.5mS / cm 2 , or greater than about 1 mS / cm 2 .

[0057] In preferred embodiments, the cathode composition contains no carbon or contains a small amount of carbon (e.g., no more than 5.0 wt. %, no more than 3.0 wt. %, no more than 2.0 wt. %, no more than 1.0 wt. %, no more than 0.5 wt. %, or no more than 0.1 wt. %). In certain embodiments, the cathode composition contains a conductive material and a binder. In certain embodiments, the conductive material includes a conductive material that facilitates the movement of electrons within the composite material. For example, in certain embodiments, the conductive material is selected from the group consisting of: carbon-based materials, graphite-based materials, conductive polymers, metals, semiconductors, metal oxides, metal sulfides, and combinations thereof, wherein non-carbon materials are preferred.

[0058] In certain embodiments, the cathode further comprises a coating. For example, in certain embodiments, the coating comprises a polymer, an organic material, an inorganic material, or a mixture thereof, which is not an integral part of the porous composite material or the current collector.

[0059] In certain embodiments, the cathode includes one or more of the following features: (a) a "stack" of multifunctional materials (e.g., where the stack includes, for example, particles having a gradient structure that balances the transport of ions and electrons for improved power capability, energy density, and life; a bifunctional cathode additive that simultaneously stores lithium and conducts electrons, replacing expensive and space-consuming carbon; a binding molecule that spatially confines the electrochemical reaction that stores energy and thereby extends life; an electrolyte component that improves the basic efficiency of the electrolyte, thereby providing improved energy density; and / or a cathode design that enables higher safety and energy density); (b) a compact electrode layer; (c) a compact tertiary structure; (d) porosity control; (e) a core-shell structure; (f) a cross-linked polymer shell; (g) a self-doped polymer shell; (h) an ion-conducting binder; (i) a double-layer hybrid cathode; (j) a polymer that captures polysulfides; (k) a three-dimensional structure with a high surface area (e.g., accommodating both carbon and lithium, e.g., embedding); and (l) a three-dimensional structure in which carbon is replaced by a metal disulfide (e.g., and where the battery includes a polymer electrolyte for sulfur).

[0060] anode

[0061] In certain embodiments, the secondary sulfur battery includes a lithium anode. A lithium anode suitable for a lithium sulfur battery can be used. In certain embodiments, the anode of the secondary sulfur battery comprises a negative electrode active material, the negative electrode active material being selected from a material in which lithium is reversibly embedded, a material that reacts with lithium ions to form a lithium-containing compound, metallic lithium, a lithium alloy, and a combination thereof. In certain embodiments, the anode comprises metallic lithium. In certain embodiments, the lithium-containing anode composition comprises a carbon-based compound. In certain embodiments, the carbon-based compound is selected from the group consisting of crystalline carbon, amorphous carbon, graphite, and mixtures thereof. In certain embodiments, the anode contains no carbon or contains a small amount of carbon (e.g., not more than 5.0 wt. %, not more than 3.0 wt. %, not more than 2.0 wt. %, not more than 1.0 wt. %, or not more than 0.5 wt. %). In certain embodiments, the material that reacts with lithium ions to form a lithium-containing compound is selected from the group consisting of tin oxide (SnO2), titanium nitrate, and silicon. In certain embodiments, the lithium alloy comprises an alloy of lithium and another alkali metal (e.g., sodium, potassium, rubidium, or cesium). In certain embodiments, the lithium alloy comprises an alloy of lithium and a transition metal. In certain embodiments, the lithium alloy comprises an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Ba, Ra, Al, Sn, In, Zn, Sm, La, and combinations thereof. In certain embodiments, the lithium alloy comprises an alloy of lithium and indium. In certain embodiments, the lithium alloy comprises an alloy of lithium and aluminum. In certain embodiments, the lithium alloy comprises an alloy of lithium and zinc. In certain embodiments, the anode comprises a lithium-silicon alloy. Examples of suitable lithium-silicon alloys include: Li15 Si4、Li 12 Si7、Li7Si3、Li 13 Si4 and Li 21 Si5 / Li 22 Si5. In certain embodiments, the lithium metal or lithium alloy is present in the form of a composite material with another material. In certain embodiments, such composite materials include materials such as graphite, graphene, metal sulfides or oxides, or conductive polymers.

[0062] In some embodiments, the anode is protected from redox shuttle reactions and dangerous runaway reactions by any method reported in the art, for example, by chemical passivation or by creating a protective layer on the anode surface by deposition or polymerization. For example, in certain embodiments, the anode comprises an inorganic protective layer, an organic protective layer, or a mixture thereof on the surface of lithium metal. In certain embodiments, the inorganic protective layer comprises Mg, Al, B, Sn, Pb, Cd, Si, In, Ga, lithium silicate, lithium borate, lithium phosphate, lithium phosphitride, lithium silicon sulfide, lithium borosulfide, lithium aluminum sulfide, lithium phosphosulfide, lithium fluoride, or a combination thereof. In certain embodiments, the organic protective layer comprises a conductive monomer, oligomer, or polymer. In certain embodiments, this polymer is selected from poly (p-phenylene), polyacetylene, poly (p-phenylene vinylene), polyaniline, polypyrrole, polythiophene, poly (2,5-ethylene vinylene), acetylene, poly (o-naphthalene), polyphenylene and poly (naphthalene-2,6-di-base), or a combination thereof.

[0063] In addition, in certain embodiments, during the charge and discharge of the secondary sulfur battery, inactive sulfur materials generated from the electroactive sulfur materials of the cathode adhere to the surface of the anode. As used herein, the term "inactive sulfur" refers to sulfur that cannot participate in the electrochemical reaction of the cathode, so that it does not contribute to capacity in repeated charge / discharge cycles. In certain embodiments, the inactive sulfur on the surface of the anode acts as a protective layer on such an anode. In certain embodiments, the inactive sulfur is present in the form of lithium sulfide.

[0064] It is further contemplated that the concepts of the present disclosure may be applicable to sodium-sulfur batteries. Such sodium-sulfur batteries include a sodium-based anode and an intercalation or conversion material capable of intercalating or reacting with sodium ions. Such systems are encompassed within the embodiments of the present disclosure.

[0065] It is further contemplated that the present disclosure may be applicable to batteries constructed with anode-free configurations. In certain embodiments, the manufactured battery or battery component has an anode-free configuration and includes an anode current collector (e.g., copper) and one or more of the following: (a) a thin layer of garnet, (b) a structure (e.g., a complex 3D structure) having a coating deposited by atomic layer deposition (ALD) (e.g., wherein the ALD coating includes one or more members selected from the group consisting of: lithium phosphorus oxynitride (LiPON), garnet, oxide, perovskite, sulfide, Li3BO3-Li2CO3 (LBCO), sodium superionic conductor (NASICON) and alumina); (c) a polymer (e.g., polyethylene oxide (PEO) or a block copolymer); (d) lithium phosphorus oxynitride (LiPON), and (e) a solid electrolyte interface (SEI) layer (e.g., an artificial SEI layer formed in situ).

[0066] Electrode preparation

[0067] There are many methods for making electrodes for secondary sulfur batteries. One such process, commonly referred to as a "wet process", involves adding a solid cathode material to a liquid to prepare a slurry composition. These slurries are usually in the form of a viscous liquid, which is formulated to facilitate downstream coating operations. Thorough mixing of the slurry may be very important for coating and drying operations, which can affect the performance and quality of the electrode. Suitable mixing devices include ball mills, magnetic stirrers, ultrasonic stirrers, planetary mixers, high-speed mixers, homogenizers, universal mixers, and static mixers. The liquid used to prepare the slurry can be any liquid that can evenly disperse active materials, binders, conductive materials, and any additives and can also evaporate. Suitable slurry liquids include, for example, N-methylpyrrolidone, acetonitrile, methanol, ethanol, propanol, butanol, tetrahydrofuran, water, isopropanol, dimethylpyrrolidone, propylene carbonate, γ-butyrolactone, etc.

[0068] In some embodiments, the prepared composition is coated on a current collector and dried to form an electrode. Specifically, the slurry is used to coat the conductor to form an electrode by evenly spreading the slurry on the conductor, and then in some embodiments, optionally rolling (e.g., calendering) and / or heating, as known in the art. Generally speaking, the matrix of active material and conductive material is combined together and fixed to the conductor by an adhesive. In some embodiments, the matrix comprises a polymer adhesive, such as polyvinylidene fluoride (PVDF), poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF / HFP), polytetrafluoroethylene (PTFE), Kynar 2801, Powerflex LBG, HSV 900, Styrene butadiene rubber (SBR), polyethylene oxide (PEO) or polytetrafluoroethylene (PTFE). Alternatively or additionally, in certain embodiments, a lithium salt is dispersed in the matrix to improve lithium conductivity.

[0069] In certain embodiments, the current collector is selected from the group consisting of aluminum foil, copper foil, nickel foil, stainless steel foil, titanium foil, zirconium foil, molybdenum foil, nickel foam, copper foam, carbon paper or carbon fiber sheet, polymer substrate coated with conductive metal, and / or combinations thereof.

[0070] PCT Publication Nos. WO2015 / 003184, WO2014 / 074150, and WO2013 / 040067, the entire disclosures of which are hereby incorporated by reference herein, describe various methods of making electrodes and electrochemical cells.

[0071] Partition

[0072] In certain embodiments, the secondary sulfur battery includes a separator that separates the anode and cathode and prevents direct electronic conduction between them. In certain embodiments, the separator has high lithium ion permeability. In certain embodiments, the separator has relatively low permeability to polysulfide ions dissolved in the electrolyte. In certain such embodiments, the separator as a whole inhibits or limits the passage of electrolyte-soluble sulfides between the anode portion and the cathode portion of the battery. In certain embodiments, the separator of the impermeable material is constructed to allow lithium ions to be transmitted between the anode and cathode of the battery during battery charging and discharging. In some such embodiments, the separator is porous. One or more electrolyte permeable channels that bypass or penetrate the holes in the impermeable surface of the separator can be provided to allow sufficient lithium ion flux between the anode portion and the cathode portion of the battery.

[0073] Those skilled in the art will appreciate that the optimum size of the separator must balance competing imperatives: maximally hindering polysulfide migration while allowing adequate lithium ion flux. The shape and orientation of the separator are not particularly limited other than the considerations described and depend in part on the cell configuration. For example, in some embodiments, the separator in a coin cell is substantially circular, while the separator in a pouch cell is substantially rectangular. In some embodiments, the separator is substantially flat. However, it is not excluded that a curved or other non-planar configuration may be used.

[0074] The separator can have any suitable thickness. In order to maximize the energy density of the battery, it is generally preferred that the separator is as thin and light as possible. However, the separator should be thick enough to provide sufficient mechanical robustness and ensure suitable electrical separation of the electrodes. In certain embodiments, the thickness of the separator is from about 1 μm to about 200 μm, preferably from about 5 μm to about 100 μm, and more preferably from about 10 μm to about 30 μm.

[0075] Electrolytes

[0076] In certain embodiments, the secondary sulfur battery includes an electrolyte comprising an electrolyte salt. Examples of electrolyte salts include, for example, lithium trifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium perchlorate, LiPF6, LiBF4, tetraalkylammonium salts (e.g., tetrabutylammonium tetrafluoroborate, TBABF4), room temperature liquid salts (e.g., imidazolium salts, such as 1-ethyl-3-methylimidazolium bis-(perfluoroethylsulfonyl)imide, EMIBeti), and the like.

[0077] In certain embodiments, the electrolyte comprises one or more alkali metal salts. In certain embodiments, such salts include lithium salts such as LiCF3SO3, LiClO4, LiNO3, LiPF6, LiBr, LiTDI, LiFSI and LiTFSI, or a combination thereof. In certain embodiments, the electrolyte comprises an ionic liquid such as 1-ethyl-3-methylimidazolium-TFSI, N-butyl-N-methylpiperidinium-TFSI, N-methyl-n-butylpyrrolium-TFSI and N-methyl-N-propylpiperidinium-TFSI, or a combination thereof. In certain embodiments, the electrolyte comprises a superionic conductor such as a sulfide, an oxide and a phosphate, for example phosphorus pentasulfide, or a combination thereof.

[0078] In certain embodiments, the electrolyte is a liquid. For example, in certain embodiments, the electrolyte comprises an organic solvent. In certain embodiments, the electrolyte comprises only one organic solvent. In some embodiments, the electrolyte comprises a mixture of two or more organic solvents. In certain embodiments, the organic solvent mixture comprises one or more weak polar solvents, strong polar solvents, and lithium protection solvents.

[0079] As used herein, the term "weak polar solvent" is defined as a solvent that can dissolve elemental sulfur and has a dielectric constant of less than 15. Weak polar solvents are selected from aromatic compounds, bicyclic ethers, and acyclic carbonate compounds. Examples of weak polar solvents include xylene, dimethoxyethane, 2-methyltetrahydrofuran, diethyl carbonate, dimethyl carbonate, toluene, dimethyl ether, diethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc. As used herein, the term "strong polar solvent" is defined as a solvent that can dissolve lithium polysulfide and has a dielectric constant greater than 15. Strong polar solvents are selected from bicyclic carbonate compounds, sulfoxide compounds, lactone compounds, ketone compounds, ester compounds, sulfate compounds, and sulfite compounds. Examples of strong polar solvents include hexamethylphosphorus triamide, γ-butyrolactone, acetonitrile, ethylene carbonate, propylene carbonate, N-methylpyrrolidone, 3-methyl-2-oxazolidinone, dimethylformamide, cyclopentane, dimethylacetamide, dimethyl sulfoxide, dimethyl sulfate, ethylene glycol diacetate, dimethyl sulfite, ethylene glycol sulfite, etc. As used herein, the term "lithium protection solvent" is defined as a solvent that forms a good protective layer (i.e., a stable solid electrolyte interface (SEI) layer) on the lithium surface and exhibits a circulation efficiency of at least 50%. The lithium protection solvent is selected from saturated ether compounds, unsaturated ether compounds, and heterocyclic compounds containing one or more heteroatoms selected from the group consisting of N, O and / or S. Examples of lithium protection solvents include tetrahydrofuran, 1,3-dioxolane, 3,5-dimethylisoxazole, 2,5-dimethylfuran, furan, 2-methylfuran, 1,4-oxacyclohexane, 4-methyldioxolane, etc.

[0080] In certain embodiments, the electrolyte is a liquid (e.g., an organic solvent). In some embodiments, the liquid is selected from the group consisting of organic carbonates, ethers, sulfones, water, alcohols, fluorocarbons, or a combination of any of these substances. In certain embodiments, the electrolyte comprises an ether solvent.

[0081] In certain embodiments, the organic solvent comprises an ether. In certain embodiments, the organic solvent is selected from the group consisting of: 1,3-dioxolane, dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, γ-butyrolactone, γ-valerolactone, and combinations thereof. In certain embodiments, the organic solvent comprises a mixture of 1,3-dioxolane and dimethoxyethane. In certain embodiments, the organic solvent comprises a 1:1 volume / volume mixture of 1,3-dioxolane and dimethoxyethane. In certain embodiments, the organic solvent is selected from the group consisting of: diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, γ-butyrolactone, γ-valerolactone, and combinations thereof. In certain embodiments, the electrolyte comprises sulfolane, sulfone, dimethyl sulfone, methyl ethyl sulfone, or a combination thereof. In some embodiments, the electrolyte comprises ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or a combination thereof.

[0082] In certain embodiments, the electrolyte is solid. In certain embodiments, the solid electrolyte comprises a polymer. In certain embodiments, the solid electrolyte comprises glass, ceramic, inorganic composite material, or a combination thereof. In certain embodiments, the solid electrolyte comprises a polymer composite material with glass, ceramic, inorganic composite material, or a combination thereof. In certain embodiments, such solid electrolytes comprise one or more liquid components as a plasticizer or form a "gel electrolyte".

[0083] Secondary sulfur battery

[0084] Secondary sulfur batteries including the above-described cathode compositions are described herein. For example, in certain embodiments, such batteries include a lithium-containing anode composition coupled to a provided cathode composition via a lithium-conducting electrolyte. In some embodiments, such batteries also include additional components such as a separator between the anode and cathode, anode and cathode current collectors, terminals that can couple the battery to an external load, and packaging such as a flexible bag or a rigid metal container. It is further contemplated that the present disclosure regarding secondary sulfur batteries can be applied to sodium-sulfur batteries, and such batteries are also considered to be within the scope of certain embodiments of the present disclosure.

[0085] Figure 1 A cross section of an electrochemical cell 800 according to an exemplary embodiment of the present disclosure is illustrated. The electrochemical cell 800 includes a negative electrode 802, a positive electrode 804, a separator 806 between the negative electrode 802 and the positive electrode 804, a container 810, and a fluid electrolyte 812 in contact with the negative electrode 802 and the positive electrode. Such a cell optionally includes additional electrode layers and separators 802a, 802b, 804a, 804b, 806a, and 806b.

[0086] The negative electrode 802 (sometimes also referred to herein as the anode) comprises a negative electrode active material that can accept cations. Non-limiting examples of negative electrode active materials for lithium-based electrochemical cells include lithium metal, lithium alloys (such as Si, Sn, Bi, In and / or Al alloys), Li4Ti5O 12 , hard carbon, graphite carbon, metal chalcogenide and / or amorphous carbon. According to some embodiments of the present disclosure, when the electrochemical cell 800 is initially manufactured, a majority (e.g., greater than 90 wt%) of the anode active material may be initially contained in the discharge positive electrode 804 (also sometimes referred to as the cathode), such that the electrode active material forms part of the first electrode 802 during the first charge of the electrochemical cell 800.

[0087] One technique for depositing electroactive material on a portion of negative electrode 802 is described in U.S. Patent Publication Nos. 2016 / 0172660 and 2016 / 0172661 (in the name of Fischer et al.), the contents of each of which are hereby incorporated by reference herein to the extent such contents are not inconsistent with the present disclosure.

[0088] Positive electrode 804 (also referred to herein as cathode) comprises a cathode composition as described herein. In certain embodiments, the cathode composition comprises about 30 to about 70% by weight of electroactive sulfur. In certain embodiments, the cathode comprises at least about 70% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 80% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 90% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 95% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises at least about 99% of the total sulfur present in the electrochemical cell. In certain embodiments, the cathode comprises substantially all of the total sulfur present in the electrochemical cell.

[0089] Negative electrode 802 and positive electrode 804 may also include one or more conductive additives as described herein. According to some embodiments of the present disclosure, negative electrode 802 and / or positive electrode 804 also include one or more polymer binders as described herein.

[0090] Figure 2 Examples of batteries according to various embodiments described herein are illustrated. For illustrative purposes, cylindrical batteries are shown here, but other types of arrangements, including square batteries or pouch (laminated) batteries, may also be used as desired. Example lithium battery 901 includes a negative electrode 902, a positive electrode 904, a separator 906 between the negative electrode 902 and the positive electrode 904, an electrolyte (not shown) impregnating the separator 906, a battery shell 905, and a seal 908 sealing the battery shell 905. It should be understood that the example battery 901 can embody multiple aspects of the present disclosure in various designs at the same time.

[0091] The secondary sulfur battery of the present disclosure includes a lithium anode, a porous sulfur-based cathode, and an electrolyte that allows lithium ions to be transported between the anode and the cathode. In certain embodiments described herein, the anode portion of the battery comprises an anode and a portion of the electrolyte in contact with it. Similarly, in certain embodiments described herein, the cathode portion of the battery comprises a cathode and a portion of the electrolyte in contact with it. In certain embodiments, the battery includes a lithium ion permeable separator that defines a boundary between the anode portion and the cathode portion. In certain embodiments, the battery includes a housing that surrounds the anode portion and the cathode portion. In certain embodiments, the battery housing includes a conductive anode end cap electrically connected to the anode and a conductive cathode end cap electrically connected to the cathode to facilitate charging and discharging via an external circuit.

[0092] In certain embodiments, the secondary sulfur batteries of the present disclosure are defined according to the ratio of their electrolyte to electroactive sulfur. The electrolyte volume and the ratio of electrolyte to sulfur in the cathode (volume / weight) are related to the energy density of the sulfur battery. The electrolyte can be distributed in different volumes within the battery, for example, the electrolyte can be contained in the pores of the cathode, in the separator, and in contact with the anode or in the anode solid electrolyte interphase. The electrolyte can also be contained in other spaces within the battery that are not in direct contact with the anode or cathode active materials-for example, the electrolyte can be retained in an annular volume at the edge of a coin cell. In certain embodiments, the present invention provides batteries in which all or most of the electrolyte is contained in the cathode. Preferably, substantially all of the electrolyte is contained in the cathode, and only the minimum amount of electrolyte required to wet the separator and the anode surface or SEI is located outside the cathode. The electrolyte contained in the cathode is referred to as the "contained electrolyte" and its volume V CE It can be estimated as the theoretical pore volume, or porosity multiplied by the geometric volume of the cathode membrane:

[0093] V CE =P%× 面积 ×Thickness 阴极

[0094] In certain embodiments, provided secondary sulfur batteries are characterized by a total electrolyte inventory (V tot ) is contained in the cathode (e.g. V CE / V tot >0.5). In certain embodiments, provided secondary sulfur batteries are characterized by a total electrolyte inventory (V tot ) is contained in the cathode (e.g. V CE / V tot>0.8). In certain embodiments, the secondary sulfur battery has at least 60%, at least 65%, or at least 70% of the electrolyte contained in the cathode porosity. In certain embodiments, the secondary sulfur battery has at least 80%, at least 85%, or at least 90% of the electrolyte contained in the cathode porosity. In certain embodiments, the secondary sulfur battery has at least 92%, at least 94%, at least 95%, at least 96%, or at least 97% of the electrolyte contained in the cathode.

[0095] The total electrolyte to sulfur ratio (E / S) is another parameter that affects the battery energy density. The E / S ratio is based on the total electrolyte volume V tot and the mass of electroactive sulfur (m 硫 ) calculated as:

[0096]

[0097] In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 6 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 5 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 4.5 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 3.5 microliters of electrolyte per milligram of electroactive sulfur / mg of electroactive sulfur or less than about 3.0 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 3.5 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is equal to or less than about 3 microliters of electrolyte per milligram of electroactive sulfur. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is between about 1.8 and about 3.5 μL / mg S. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is between about 1.8 and about 2.5 μL / mg S. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is between about 1.0 and about 2.0 μL / mg S. In certain embodiments, the electrolyte to sulfur ratio of the secondary sulfur battery is between about 1.5 and about 2.0 μL / mg S.

[0098] Equivalent solutions

[0099] It is contemplated that the systems, apparatuses, methods, and processes of the present disclosure encompass variations and adaptations developed using information from the embodiments described herein.Adaptations and / or modifications of the systems, apparatuses, methods, and processes described herein may be performed by one of ordinary skill in the relevant art.

[0100] Certain embodiments of the present disclosure are described above. However, it is expressly pointed out that the present disclosure is not limited to those embodiments, but additions and modifications to the contents explicitly described in the present disclosure are also intended to be included within the scope of the present disclosure. In addition, it should be understood that the features of the various embodiments described in the present disclosure are not mutually exclusive, and may exist in various combinations and arrangements without departing from the spirit and scope of the present disclosure, even if these combinations or arrangements have not been expressed. The present disclosure has been described in detail with specific reference to certain embodiments of the present disclosure, but it should be understood that changes and modifications may be achieved within the spirit and scope of the claimed invention.

Claims

1. A cathode material for a carbon-free sulfur cathode, the cathode material comprising: at least one electroactive sulfur conversion cathode material; and Non-sulfur, non-carbon electroactive materials, Wherein the cathode material (e.g., and wherein the carbon-free cathode) contains no more than 5 wt. % (e.g., no more than 2 wt. %, no more than 1 wt. %, no more than 0.5 wt. % or no more than 0.1 wt. %) carbon.

2. The cathode material of claim 1, wherein the non-sulfur, non-carbon electroactive material is an intercalation material having a voltage range that overlaps with the voltage range of sulfur conversion (e.g., about 1.8 V to about 2.6 V, relative to Li / Li + , for example, about 2.0 V to about 2.4 V, relative to Li / Li + ) structure that can reversibly embed lithium ions.

3. The cathode material of claim 1, wherein the non-sulfur, non-carbon electroactive material is a conversion material (e.g., in a voltage range overlapping with the voltage range for sulfur conversion (e.g., about 1.8 V to about 2.6 V, relative to Li / Li + , for example, about 2.0 V to about 2.4 V, relative to Li / Li + ) chalcogenides that undergo electrochemical conversion reactions).

4. The cathode material of any one of the preceding claims, wherein the non-sulfur, non-carbon electroactive material is a chalcogenide (eg, a metal chalcogenide, eg, a metal sulfide).

5. The cathode material of any preceding claim, wherein the non-sulfur, non-carbon electroactive material is also an electron conductor.

6. The cathode of any one of the preceding claims, wherein the non-sulfur, non-carbon electroactive material has a discharge capacity.

7. A cathode material as claimed in any preceding claim comprising a core-shell structure.

8. The cathode material of claim 7, comprising a core each having a surrounding shell, the core comprising the electroactive sulfur conversion material (e.g., Li2S2 and / or Li2S), and the shell comprising the non-sulfur, non-carbon electroactive material (e.g., one or more metal chalcogenides).

9. The cathode material of claim 7 or 8, wherein the core-shell structure has an average core diameter in the range of 50 to 300 nm and an average shell thickness in the range of 1 to 20 nm thick (e.g., no more than 10 nm thick).

10. The cathode material of any one of claims 7 to 9, wherein the core-shell structure has at least 10 mass % of non-sulfur, non-carbon electroactive material (e.g., metal chalcogenide) relative to sulfur (e.g., 10 to 90 mass % of non-sulfur, non-carbon electroactive material, e.g., 30 to 70 mass % of non-sulfur, non-carbon electroactive material).

11. A cathode material as described in any of the preceding claims, wherein the at least one electroactive sulfur-conversion cathode material comprises one or more members selected from the group consisting of sulfur in the form of an S8 cyclic octaatomic molecule, lithium sulfide (e.g., Li2S2 and / or Li2S), an electroactive organic sulfur compound, and an electroactive sulfur-containing polymer.

12. A cathode comprising the cathode material of any one of claims 1 to 11, wherein the fraction of carbon in the cathode does not exceed 5 wt% (e.g., not more than 2 wt%, not more than 1 wt%, not more than 0.5 wt%, or not more than 0.1 wt%).

13. The cathode of claim 12, wherein the cathode material is provided in a thin film (eg, comprising a binder).

14. A battery (eg, a rechargeable battery) comprising (i) a cathode as claimed in claim 12 or claim 13 and (ii) an electrolyte in contact with the cathode.

15. The battery of claim 14, further comprising an anode.

16. The battery of claim 15, wherein the anode is a protected lithium metal anode.

17. The battery of claim 14, further comprising a protected current collector.

Citation Information

Patent Citations

  • 3D self-assembled multi-modal carbon-based particles integrated into a continuous electrode film layer

    US11299397B2

  • Electrochemical cell and method of making the same

    US20160172660A1

  • Electrochemical cell and method of making the same

    US20160172661A1

  • Encapsulated sulfur cathodes for rechargeable lithium batteries

    WO2013040067A1

  • Core-shell structured nanoparticles for lithium-sulfur cells

    WO2014074150A1